2018
DOI: 10.3847/1538-3881/aa9f27
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Abundances of Kepler Objects of Interest in APOGEE. I. Two Distinct Orbital Period Regimes Inferred from Host Star Iron Abundances

Abstract: The Apache Point Observatory Galactic Evolution Experiment (APOGEE) has observed ∼600 transiting exoplanets and exoplanet candidates from Kepler (Kepler Objects of Interest, KOIs), most with 18 epochs. The combined multi-epoch spectra are of high signal-to-noise ratio (typically 100) and yield precise stellar parameters and chemical abundances. We first confirm the ability of the APOGEE abundance pipeline, ASPCAP, to derive reliable [Fe/H] and effective temperatures for FGK dwarf stars-the primary Kepler host … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 112 publications
(189 reference statements)
9
50
0
Order By: Relevance
“…However, these results were contested by Mulders et al [192] who argued that the observed trends might be due to selection effects. A systematic excess of short period ( 10 days) rocky planets (< 1.7 R ⊕ ) around metal-rich stars was reported in several works [139,192,288]. The metallicity preference of hot rocky planets is explained by the possible dependence of efficient inward migration of solids on metallicity [139], higher rates of planet-planet scattering in metal-rich disks [139], and/or dependence of planet trap at the inner age on metallicity [192,288].…”
Section: Low-mass Planets and Metallicitymentioning
confidence: 87%
See 1 more Smart Citation
“…However, these results were contested by Mulders et al [192] who argued that the observed trends might be due to selection effects. A systematic excess of short period ( 10 days) rocky planets (< 1.7 R ⊕ ) around metal-rich stars was reported in several works [139,192,288]. The metallicity preference of hot rocky planets is explained by the possible dependence of efficient inward migration of solids on metallicity [139], higher rates of planet-planet scattering in metal-rich disks [139], and/or dependence of planet trap at the inner age on metallicity [192,288].…”
Section: Low-mass Planets and Metallicitymentioning
confidence: 87%
“…When studying the metallicity dependence of low-mass/small size planets it is very important to take into account the relation between orbital periods of planets and their host stars metallicities [116,139,161,192,[286][287][288][289]. In particular, Adibekyan et al [161] found that the super-Earth-like planets (M sin i < 10 M ⊕ ) orbiting metal-rich stars have orbital periods shorter than about 20 days, whereas planets orbiting metal-poor stars span a wide range of orbital periods [see also 116,287].…”
Section: Low-mass Planets and Metallicitymentioning
confidence: 99%
“…Planet occurrence rates as a function of spectroscopic metallicity were calculated by Mulders et al (2016) for a sample of 20,000 Kepler target stars with medium resolution spectroscopy from Frasca et al (2016). They find no difference in the occurrence rate of sub-Neptunes as a function of metallicity, except at orbital periods smaller than 10 days (see also Wilson et al 2017;Petigura et al 2017a). This elevated occurrence rate at short orbital periods is consistent with the higher detection frequency of sub-Neptunes around metal-rich stars (Wang and Fischer 2015;Zhu et al 2016).…”
Section: A Wide Range Of Stellar Metallicity For Sub-neptunesmentioning
confidence: 99%
“…Finally, an increasing number of studies have pointed towards the existence of correlations between the properties of the host stars and the characteristics and frequency of their planetary systems. In this respect, the correlation between the stellar metallicity and the frequency of giant planets [41,49,64], the connection between radius vs metallicity [13,43], eccentricity vs metallicity [3,67], the role of the abundances of other elements [4,16,17] in the host stars are only few examples of different results that take a clear shape as the new planet discoveries increase, shading light on many details still missing concerning planet formation and evolution.…”
Section: Introductionmentioning
confidence: 99%